147k views
1 vote
What is the solution to the following system of equations? x − 4y = 6 2x + 2y = 12

User Joann
by
4.5k points

1 Answer

1 vote

Answer:

(6, 0 )

Explanation:

Given the 2 equations

x - 4y = 6 → (1)

2x + 2y = 12 → (2)

Rearrange (1) expressing x in terms of y by adding 4y to both sides

x = 6 + 4y → (3)

Substitute x = 6 + 4y into (2)

2(6 + 4y) + 2y = 12 ← distribute and simplify left side

12 + 8y + 2y = 12

10y + 12 = 12 ( subtract 12 from both sides )

10y = 0 ⇒ y = 0

Substitute y = 0 into (3) for corresponding value of x

x = 6 + 4(0) = 6 + 0 = 6

Solution is (6, 0 )

User Dimarzionist
by
4.9k points